Overlooked : Examining the Impact of Disasters and Climate Shocks on Poverty in the Europe and Central Asia Region - World Bank (Washington, DC: World Bank, 2022)
When a disaster strikes, it not only affects households’ physical assets, but also their income levels and ability to contribute to the local economy. Critically, these socio-economic disparities shape not only the severity of shocks on household-level economies, but also the duration of subsequent recovery and reconstruction efforts. Socio-economic characteristics may therefore help to determine in advance which households or communities are more likely to recover faster, and which are in need of external assistance to accelerate reconstruction efforts. This report explores the links between disaster impacts and poverty levels in select countries in the Europe and Central Asia region.